A GIS-based LVF model for semiquantitative assessment of groundwater pollution risk: A case study in Shenyang, NE China. Issue 2 (17th February 2017) - Zhang, Junjun; Zhai, Yuanzheng; Xue, Pengwei; Huan, Huan; Zhao, Xiaobing; Teng, Yanguo; Wang, Jinsheng
ABSTRACT: Groundwater pollution risk assessment is a useful tool to prevent and control groundwater pollution, but its quantitative research is still relatively immature. In this study, a geographic information system based LVF model for a semiquantitative assessment of groundwater pollution risk is established, based on the groundwater pollution source load (L), groundwater vulnerability (V), and groundwater function value (F). Further, the pollution source load is characterized by seven specific pollution sources, the vulnerability is calculated by the modified DRASTIC method, and the groundwater function value is evaluated with the water quality and quantity. The model was used to assess the risk of shallow groundwater pollution in Shenyang city, Northeast China, with an area of 8, 263 km 2 . The results show that highest risk areas account for 16.3% of the study area and are mainly distributed in the east of the study area. High risk areas are significantly affected by a shallow buried depth of groundwater and many types of harmful pollutants from industrial, agricultural, and domestic pollution sources. The evaluation results reflect the risk of groundwater pollution in the Shenyang area, which is relevant to the management and sustainable use of groundwater resources in the area.